Pengaruh Perbandingan Konsentrasi Tepung Agar-Agar dan Biji Chia (Salvia Hispanica L.) terhadap Sifat Fisikokimia dan Sensori Fruit Leather Terong Belanda (Solanum Betaceum Cav.) - Anggraini, Fitri Dwi; Puspawati, Gusti Ayu Kadek Diah; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Fruit leather is a processed dried fruit in the form of thin sheets that can be rolled up. One of the fruits that can be processed into fruit leather is dutch eggplant. The elasticity of fruit leather is influenced by the binder used. The use of seaweed pulp binder in dutch eggplant fruit leather requires a long preparation time. One of the natural ingredients that has the potential to be used as a binder and is easy to prepare is chia seeds and agar-agar. The research was aimed to determine the effect of the concentration ratio of agar-agar powder and chia seeds on the physicochemical and sensory characteristics of dutch eggplant fruit leather and to determine the appropriate concentrations of agar-agar powder and chia seeds to produce dutch eggplant fruit leather with the best physicochemical and sensory characteristics. This study used a completely randomized design with a comparison of the concentrations of agar powder and chia seeds consisting of 6 levels: 100%:0%, 80%:20%, 60%:40%, 40%:60%, 20% :80%, and 0%:100% treatment was repeated 3 times. The data was analyzed with analysis of variance, and if the treatment had a significant effect, then followed by the Duncan's Multiple Range Test. The results showed that the concentration of agar-agar and chia seeds had a significant effect on tensile strength, L,a*,b* values, water content, crude fiber, flavonoids content, antioxidant activity, and sensory including hedonic tests (color, texture, overall acceptance). and scoring (texture). The best dutch eggplant fruit leather was treated with a ratio of agar- agar powder and chia seeds concentration of 40%:60% with a tensile strength value 2.18 MPa, L value 19.6, a* 15.36, b* 13.16, water content 13.55%, crude fiber 7.47%, flavonoids content 3.41mgQE/g, antioxidant activity 53.93%, color, taste, plastic texture and overall acceptance liked.